Catalytic use of layered materials for fine chemical syntheses. Issue 1 (5th December 2018) - Ötvös, Sándor B.; Pálinkó, István; Fülöp, Ferenc
Abstract : The present work reviews the catalytic use of layered solid materials for fine chemical syntheses with focus on layered double hydroxides, but including other classes of layered compounds of catalytic relevance. Abstract : The present work reviews the catalytic use of layered solid materials for fine chemical syntheses with focus on layered double hydroxides, but including other classes of layered compounds of catalytic relevance. Catalytic applications are surveyed, in which the layered catalyst structure is preserved as a significant asset in potentiating the catalytic transformations. Original contributions do exist in this area; however, their number is significantly smaller than that of heat-treated layered catalytic materials. The advances made during the past decade are summarized herein.